The areas of virtual educational supervision used in communication and developing the administrative performance of school leaders in the southern Taif region during the Corona pandemic - Al-Maliki, Sharifeh Abdullah (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the areas of virtual educational supervision used in communication and developing the administrative performance of school leaders in the south of Taif during the Corona pandemic, and the impact of variables (job title, educational qualification, experience); In the sample estimates of the degree of effectiveness of virtual educational supervision. The researcher used the descriptive survey method, and the tool consisted of a questionnaire consisting of (19) phrases distributed over three areas that were applied to a deliberate stratified sample of (52) supervisors and school leaders from the south of Taif, and the results of the study showed that the degree of effectiveness of virtual educational supervision in developing performance. The administrative staff of school leaders- from the sample’s point of view- got an overall average (3.86 out of 5), i.e., with a (high) degree of effectiveness and at the level of the domains; The domain of using the web got the highest average (4.13), followed by the domain of using e- mail with an average of (3.79), both with a degree of effectiveness (great), and finally the domain of using conversation with an average of (3.65) and an evaluation of effectiveness (medium). The results of the study also showed no significant differences. Statistical significance at the level (α ≤ 0.05) among the study sample members' estimates of the effectiveness of virtual educational supervision in developing the administrative performance of school leaders in the south of Taif, due to the variables (job title, educational qualification, experience). Based on the results, the researcher presented a number of recommendations and proposals to improve the effectiveness of virtual educational supervision and develop the administrative performance of school leaders in the south of Taif and all regions of the Kingdom.
Keywords: Virtual Supervision; Administrative Performance Development; South Taif; School Leaders; Corona